# Multiplication of two Taylor expansions [closed]

I'm trying to calculate a Taylor expansion which is : $\cos(x). exp(x)$ in the neighborhood of 0 in order 3

this is the result I got :

$$\cos(x). exp(x) = \left(1-\frac{x²}{2}+\epsilon(x)x^3\right) . \left(1+x+\frac{x²}{2}+\frac{x^3}{6}+\epsilon(x)x^3\right)$$

And now I need to multiply the two expressions.

I think that there is a method where we use a table to multiply to Taylor expansion, but I don't know hw to do it.

-

## closed as off-topic by M. Vinay, Shaun, Shailesh, Math1000, Daniel W. FarlowJun 29 at 1:05

This question appears to be off-topic. The users who voted to close gave this specific reason:

• "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – M. Vinay, Shaun, Shailesh, Math1000, Daniel W. Farlow
If this question can be reworded to fit the rules in the help center, please edit the question.

Can you multiply polynomials? think series expansions as polynomials with possibly infinite degree – Federica Maggioni May 1 '13 at 16:36
@FedericaMaggioni sorry I didn't understand what you mean – Aimad Majdou May 1 '13 at 16:41
Throw away the tiny terms at the end. Just multiply the binomial $(1-x^2/2)$ and the tetranomial $(1+x+x^2/2+x^3/6)$. Since you're not considered with any terms of degree $>3$, they won't matter. Following that multiplication, throw out the terms you get from that product of degree $>3$. – Ian Coley May 1 '13 at 16:45
Possible duplicate of Multiplying Taylor series and composition – PHPirate Jun 28 at 9:31

Why don't you use regular definition $$\hat f(x)=f(x=0)+f'(x=0)x+\frac 12 f''(x=0)x^2+\frac 16 f'''(x=0)x^3+O(x^4)$$ where $$f(x=0)=e^x \cos(x)=1$$ $$f'(x=0)=e^x \cos(x)-e^x \sin(x)=1$$ $$f''(x=0)=-2e^x \sin(x)=0$$ $$f'''(x=0)=-2e^x \cos(x)-2e^x \sin(x)=-2$$ and $$\hat f(x)=1+x-\frac 26 x^3+O(x^4)$$
You use the distributive property, so the expansion starts off $1\cdot 1 +1\cdot x +1 \cdot \frac {x^2}2 -\frac {x^2}2\cdot 1$, then collect the terms of the same degree